Potential Failure Mode Analysis - World Bank (World Bank, Washington, DC, 2021)
Potential failure modes analysis (PFMA) is a process to systematically identify, describe, and evaluate the ways in which a dam and its appurtenant structures could fail under postulated loading conditions. Since 2002, PFMA has been introduced as part of five-year inspections under the U.S. Federal Energy Regulatory Commission (FERC) regulations for nonfederal hydropower dams in the United States. The PFMA is intended to provide an understanding of how and why dams fail by looking at how dams behave normally, learning to identify early signs that something is wrong, understanding the hazards and risks imposed by the dam, and being prepared for the unexpected behavior that leads to failure. The World Bank has assisted some countries in applying the PFMA for safety review of major existing dams and found that the tool is useful in prioritizing additional investigations needs and remedial works in coordination with key stakeholders, including owners, operators, and designers. This Technical Note contains guidance for preparing PFMA terms of reference for: (a) the FERC-based standard approach to PFMA; and (b) a simplified PFMA approach.